Age Distribution of Bone Mineral Density According to Quantitative Computed Tomography - A. V. Petraikin; F. A. Petriaikin; К. A. Sergunova; L. A. Nizovtsova; E. S. Akhmad; D. S. Semenov; N. S. Polishchuk; S. P. Morozov; A. V. Vladzymyrskyy (Вестник рентгенологии и радиологии, 2019)
Objective. To compare bone mineral density (BMD) values derived during one-year asynchronous quantitative computed tomography (QCT) in two urban polyclinics (UPs).Material and methods. The investigation enrolled women aged 40 to 85 years: 694 and 724 patients in UP А and UP B, respectively, who underwent QCT scanning of the proximal femur and spine. The BMD values were compared with the reference data embedded in the QCP software, by using the methods of regression analysis. Quantitative indicators were calculated using the Z-test. To standardize the indicators of QCT in UP A and UP B, cross-calibration was performed using a phantom.Results. Comparison of the obtained mean BMD values with the reference one for three regions of central densitometry established a statistically significant (p<0.05) decrease in the mean BMD values relative to the normative ones within the analyzed age range. The spine Z scores were  – 0.37 SD in UP А and  – 0.84 SD in UP B; the mean proximal femur Z scores were  – 0.70 SD and  – 1.22 SD in UP А and UP B, respectively; the mean femoral neck Z scores were  – 0.54 SD and  – 1.06 SD, respectively. The values of femoral neck and proximal femur BMD displayed pronounced correlations (r=0.83 in UP А and r=0.79 in UP B). Comparison of regression line coefficients in the proximal femur and spine regions revealed that the offset of a straight line was significantly lower in UP B than in UP А (p<0.05). There were no differences in the slope coefficients for these regions. The results of comparing the regression lines for the femoral neck were statistically insignificant for both the slope coefficient (p=0.576) and for the offset (p=0.056).Conclusion. Comparison of the authors' own results of the BMD study with the reference data has shown a statistically significant decrease in the obtained BMD values in two UPs. This may be associated with the different strategy of referral for QCT, as well as with some assumptions of this study.